2008
DOI: 10.1016/j.ydbio.2008.05.522
|View full text |Cite
|
Sign up to set email alerts
|

The receptor phosphatase HmLAR2 collaborates with focal adhesion proteins in filopodial tips to control growth cone morphology

Abstract: Receptor protein tyrosine phosphatases (RPTPs) have been shown to play key roles in regulating axon guidance and synaptogenesis. HmLAR2, one of two closely related LAR-like RPTPs in the embryonic leech, is expressed in a few central neurons and in a unique segmentally-iterated peripheral cell, the comb cell (CC). Here we show that tagged HmLAR2-EGFP has a punctate pattern of expression in the growth cones of the CC, particularly at the tips of extending filopodia. Moreover, although expression of the wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In this regard, it is significant that NO can play a major role in control of growth cone movement and motility (Tornieri et al, 2007; Welshhans et al, 2007). Whether some of the interactions between growth cones that influence their movement (Shain et al, 2004; Baker et al, 2007; Baker et al, 2008) are also important for guidance of microglial migration is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is significant that NO can play a major role in control of growth cone movement and motility (Tornieri et al, 2007; Welshhans et al, 2007). Whether some of the interactions between growth cones that influence their movement (Shain et al, 2004; Baker et al, 2007; Baker et al, 2008) are also important for guidance of microglial migration is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid injections into nuclei of post-mitotic cells have been used in late stage embryos of the medicinal leech Hirudo to express reporter constructs as well as for functional studies, (Baker and Macagno, 2006; Shefi et al, 2006; Baker and Macagno, 2007; Baker et al, 2008). Previous attempts to drive ectopic gene expression in the early Helobdella embryo using plasmid injections were problematic, however; expression was highly mosaic (i.e., was seen in only a few of the progeny of the injected cell) and the injected lineage developed abnormally independent of the expression of the transgene…”
Section: Introductionmentioning
confidence: 99%
“…yet been established in any oligochaete species, while four experiments have so far been reported on another order of annelids (leech, Hirudinea) (Baker et al, 2008;Shefi et al, 2006;Biswas et al, 2002;Baker and Macagno., 2000). In the analysis utilizing RNAi, a variety of animals are soaked in, injected with, or fed with RNA solutions to make their cells incorporate dsRNA or siRNA.…”
Section: Functional Analysis Of a Novel Gene Grimp In E Japonensis 157mentioning
confidence: 99%
“…Although molecular biological research on regeneration has been conducted in oligochaetes (Niva et al, 2008;Takeo et al, 2008;Myohara et al, 2006;Tadokoro et al, 2006;Martinez et al, 2005;Bely and Wray, 2001;Dupin et al, 1991), gene knock-downs have not yet been succeeded. So far, only four studies utilizing RNAi in other orders of annelids (leech, Hirudinea) have been reported (Baker et al, 2008;Shefi et al, 2006;Biswas et al, 2002;Baker and Macagno, 2000).…”
Section: Introductionmentioning
confidence: 99%